Improvement in Functional Outcome from 6 to 12 Months After Moderate and Severe Traumatic Brain Injury Is Frequent, But May Not Be Detected With the Glasgow Outcome Scale Extended - Rabea Iris Pantelatos; Jonas Stenberg; Turid Follestad; Oddrun Sandrød; Cathrine Elisabeth Einarsen; Anne Vik; Toril Skandsen (Neurotrauma Reports)
The aims of this study were (1) to report outcome and change in outcome in patients with moderate and severe traumatic brain injury (mo/sTBI) between 6 and 12 months post-injury as measured by the Glasgow Outcome Scale Extended (GOSE), (2) to explore if demographic/injury-related variables can predict improvement in GOSE score, and (3) to investigate rate of improvement in Disability Rating Scale (DRS) score, in patients with a stable GOSE. All surviving patients ≥16 years of age who were admitted with mo/sTBI (Glasgow Coma Scale [GCS] score ≤13) to the regional trauma center in Central Norway between 2004 and 2019 were prospectively included (n = 439 out of 503 eligible). GOSE and DRS were used to assess outcome. Twelve-months post-injury, 13% with moTBI had severe disability (GOSE 2–4) versus 27% in sTBI, 26% had moderate disability (GOSE 5–6) versus 41% in sTBI and 62% had good recovery (GOSE 7–8) versus 31% in sTBI. From 6 to 12 months post-injury, 27% with moTBI and 32% with sTBI had an improvement, whereas 6% with moTBI and 6% with sTBI had a deterioration in GOSE score. Younger age and higher GCS score were associated with improved GOSE score. Improvement was least frequent for patients with a GOSE score of 3 at 6 months. In patients with a stable GOSE score of 3, an improvement in DRS score was observed in 22 (46%) patients. In conclusion, two thirds and one third of patients with mo/sTBI, respectively, had a good recovery. Importantly, change, mostly improvement, in GOSE score between 6 and 12 months was frequent and argues against the use of 6 months outcome as a time end-point in research. The GOSE does, however, not seem to be sensitive to actual change in function in the lower categories and a combination of outcome measures may be needed to describe the consequences after TBI.